Specificity of strength training exercises to the sprint run and vertical jump tests - Blazevich, A. J.; Newton, R. U.; Sharman, M.; Bronks, R.; Gill, N. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Adaptations to resistance exercise appear to be specific to the movement patterns of the training exercises. Therefore tests such as the 20m sprint and vertical jump are problematic in that their movement patterns may be different from the exercises used in training. The purpose of the present study therefore was three-fold: 1) to determine which of several forms of the vertical jump had movement patterns most similar to the squat lift, 2) to determine whether a new exercise, coined the forward hack squat (FHS), allowed subjects to train with a movement pattern similar to the acceleration phase of sprint running, and 3) to examine relationships between subject's performances in these tests. First, a biomechanical analysis of the vertical jump (hands on hips, arms crossed over chest, hands on head, and with arm swing), squat lifts at three loads, and the FHS exercise at three loads was performed by 8 well-trained strength athletes. EMG was also used to quantify muscle contraction patterns of five lower limb muscles. Biomechanical data collected for the FHS was compared to sprint data published by Jacobs & Ingen Schenau [Intramuscular coordination during a sprint push-off. Journal of Biomechanics, 25(9), 953-965, 1992]. Sprint running was not analysed since no long-lead or telemetric EMG hardware was available. Results suggest that the vertical jump performed with the arms crossed over the chest was similar to the jump-squat exercise, but not similar to the heavy squat. The kinematics of the FHS (particularly the movement of the body centre of gravity and timing and displacement of joint angles) were similar to the acceleration phase of sprint running. The squat lift was not similar to sprint running, nor was the FHS similar to the vertical jump. Second, relationships between subject's performances in the above tasks were determined for 30 active men and women. Tests included the vertical jump, FHS (isometric and at 40% and 70% of maximum), squat (isometric and at 30% and 60% of maximum) and the 20 m sprint (10 m and 20 m sprint times). Force applied during the FHS correlated better with 20 m sprint time than force applied during the squats although all correlations were statistically significant (p<0.01). Therefore, FHS performance appeared to be a better predictor of 20 m sprint time than squat performance suggesting again that the FHS could be considered specific to the acceleration phase of sprint running. Vertical jump height was not correlated with the force produced during jump squats with loads of 30% and 60% of maximum. Given that the vertical jump used in the present study was kinematically similar to the jump squat, the result suggests that the different movement velocities between the two tasks may have affected their similarity.